What Predicts Hopelessness Among Muslim Final-Year Students in Indonesia? A Psychosocial Investigation - Putra, Ade Herdian; Bah, Yahya Muhammed; Ibrahim, Kabiru Hannafi; Bah, Ismaila S; Ardi, Zadrian (Universitas Negeri Padang, 2025)
Final year students often face high academic and psychological pressures, especially towards the completion of their studies. In the context of Muslim students in Indonesia, this situation is even more complex as they are faced with academic demands, social expectations, and spiritual dynamics that shape their psychological experience. One of the impacts of this pressure is the emergence of hopelessness, which is a feeling of hopelessness about the situation at hand. This study aims to understand the psychosocial factors that influence hopelessness in final-year Muslim students, focusing on the role of peer attachment, healthy lifestyle, social media addiction, academic stress, and religiosity. This study used a confirmatory quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. A total of 815 final-year Muslim students from various universities in Indonesia participated in the online survey. The research instrument measured six main constructs, and the data were analyzed to test the validity, reliability, direct and indirect effects, and mediating and moderating roles in the conceptual model. The results of the analysis showed that academic stress was a significant mediator in the relationship between healthy lifestyle, social media addiction, and religiosity with hopelessness. Meanwhile, religiosity also acts as a moderator that strengthens or weakens the relationship between peer attachment, academic stress, and social media addiction with hopelessness. This model is able to explain 93.6% of the variance of academic stress and 97.8% of the variance of hopelessness. However, peer attachment showed no significant direct or indirect effect on hopelessness. These findings confirm the importance of comprehensive guidance and counseling services for final year students, especially in managing academic stress, social media use, and strengthening the meaning of life. Healthy lifestyle-based interventions and targeted emotional support are needed to prevent hopelessness in this population.